Functioning outcomes with adjunctive treatments for major depressive disorder: a systematic review of randomized placebo-controlled studies - Weiller E (Dove Medical Press, 2017)
Emmanuelle Weiller,1 Catherine Weiss,2 Christopher P Watling,3 Christopher Edge,3 Mary Hobart,2 Hans Eriksson,1 Maurizio Fava4–6 1H. Lundbeck A/S, Valby, Copenhagen, Denmark; 2Otsuka Pharmaceutical Development & Commercialization Inc., Princeton, NJ, USA; 3Cambridge Medical Communication Ltd, Cambridge, UK; 4Division of Clinical Research of the MGH Research Institute, 5Department of Psychiatry, 6Clinical Trials Network & Institute (CTNI), Massachusetts General Hospital, Boston, MA, USA Objective: Patients with major depressive disorder (MDD) with inadequate response to antidepressant treatment (ADT) may suffer a prolonged loss of functioning. This review aimed to determine if self-rated functional measures are informative in randomized placebo-controlled studies of adjunctive therapy in patients with MDD and inadequate response to ADT. Methods: This was a systematic literature review of articles in any language from the MEDLINE database published between January 1990 and March 2017. Eligible studies met the following criteria: patients with MDD; inadequate response to at least one ADT; adjunctive therapy (pharmacological or otherwise) to ADT; placebo control group; randomized controlled trial or a post hoc analysis of a randomized controlled trial; reported a self-rated functioning scale. Study characteristics and functioning efficacy data were extracted. Results: A total of 2,090 discrete records were screened, 293 full-text articles were assessed for eligibility, and 26 studies were included. All studies were acute (6–12 weeks) except for one 52-week study. The only self-rated functioning scale used in the included studies was the Sheehan Disability Scale (SDS). Of the 13 adjunctive agents identified, aripiprazole, brexpiprazole, edivoxetine, and risperidone improved functioning versus placebo (p<0.05), as measured by the SDS total or mean score. On the SDS “work/studies” item, only aripiprazole had a statistically significant benefit, in one study out of four. Thus, where a benefit was observed on the SDS total or mean, this was generally driven by improvement on the “social life” and “family life” items. A limitation of the review is that it only considered published literature from one database. Conclusion: The SDS, a self-rated functional measure, is informative in acute randomized placebo-controlled studies of adjunctive therapy in patients with MDD and inadequate response to ADT. However, the item that measures work performance may be less relevant to this population than the items that measure social and family life. Keywords: depression, antidepressant, adjunct, Sheehan Disability Scale, functional, work